Professionalizing the Nation's Cybersecurity Workforce?: Criteria for Decision-Making - National Research Council (The National Academies Press, 2013)
Professionalizing the Nation's Cybersecurity Workforce? Criteria for Decision-Making considers approaches to increasing the professionalization of the nation's cybersecurity workforce. This report examines workforce requirements for cybersecurity and the segments and job functions in which professionalization is most needed; the role of assessment tools, certification, licensing, and other means for assessing and enhancing professionalization; and emerging approaches, such as performance-based measures. It also examines requirements for the federal (military and civilian) workforce, the private sector, and state and local government. The report focuses on three essential elements: (1) understanding the context for cybersecurity workforce development, (2) considering the relative advantages, disadvantages, and approaches to professionalizing the nation's cybersecurity workforce, and (3) setting forth criteria that can be used to identify which, if any, specialty areas may require professionalization and set forth criteria for evaluating different approaches and tools for professionalization. Professionalizing the Nation's Cybersecurity Workforce? Criteria for Decision-Making characterizes the current landscape for cybersecurity workforce development and sets forth criteria that the federal agencies participating in the National Initiative for Cybersecurity Education—as well as organizations that employ cybersecurity workers—could use to identify which specialty areas may require professionalization and to evaluate different approaches and tools for professionalization.
Keywords: Computers and Information Technology; Education; Industry and Labor

Critical Code: Software Producibility for Defense - National Research Council (The National Academies Press, 2010)
Critical Code contemplates Department of Defense (DoD) needs and priorities for software research and suggests a research agenda and related actions. Building on two prior books—Summary of a Workshop on Software Intensive Systems and Uncertainty at Scale and Preliminary Observations on DoD Software Research Needs and Priorities—the present volume assesses the nature of the national investment in software research and, in particular, considers ways to revitalize the knowledge base needed to design, produce, and employ software-intensive systems for tomorrow's defense needs. Critical Code discusses four sets of questions: To what extent is software capability significant for the DoD? Is it becoming more or less significant and strategic in systems development? Will the advances in software producibility needed by the DoD emerge unaided from industry at a pace sufficient to meet evolving defense requirements? What are the opportunities for the DoD to make more effective use of emerging technology to improve software capability and software producibility? In which technology areas should the DoD invest in research to advance defense software capability and producibility?
Keywords: Computers and Information Technology; Conflict and Security Issues